Consumer Protection Legal Frameworks in Indonesia: The Challenges of E-Commerce and Data Privacy - Supriyanto; Rahardjo, Tanti Malaka Sari; Sumiyati; Noerdjaja, Himawan; Pambudi, Gumilang Eka; Prabowo, M. Shidqon (Research Horizon, 2025)
Consumer protection law in Indonesia, primarily governed by Law No. 8 of 1999, aims to safeguard consumer rights amidst the complexities of a growing economy. While this law has helped address power imbalances between consumers and businesses, it faces limitations in dealing with challenges arising from the digital economy, particularly in the realms of e-commerce and data privacy. The main objective of this study is to evaluate the effectiveness of Indonesia’s consumer protection framework in the context of these modern challenges. Using a juridical-normative approach, the research analyzes relevant legal provisions through qualitative techniques, focusing on the applicability of existing laws to digital transactions. The study reveals significant gaps, particularly in the protection of personal data, cybersecurity, and privacy in e-commerce. Although various regulations, such as the Electronic Information and Transactions Law and the Trade Law, provide some safeguards, they remain insufficient in fully addressing the risks posed by rapid technological advancements. The enforcement mechanisms are also weak, leaving consumers vulnerable to issues like fraud and data breaches. The study concludes that Indonesia’s consumer protection laws must be revised to address these new challenges, with a more comprehensive and centralized framework that aligns with international standards on data protection and digital transactions.